Outline Design of ITER Radial X-Ray Camera Diagnostic. (1st July 2016) - Hu, L; Chen, K; Chen, Y; Li, S; Shen, J; Sheng, X; Niu, L; Cheng, Y; Zhao, J
Abstract: The radial X-ray camera (RXC) is designed to measure the poloidal profile of plasma X-ray emission with high spatial and temporal resolution. Its primary diagnostic role includes measuring low (m, n) magnetohydrodynamic modes, sawteeth and disruption precursors, H-mode, edge-localized modes, and L-H transition. The RXC comprises two subsystems, i.e., in-port and ex-port cameras that view the outer and core regions, respectively, through vertical slots in the diagnostics shield module of an equatorial port plug. Detailed camera design is in progress including design of the camera structure, electronics, data acquisition and control, calibration, and pretest on the EAST tokamak. The sight path and neutron shielding have been optimized. The secondary vacuum, heat insulation, cooling, positioning, and calibration have been designed. The structure analysis results for the external camera indicate that even under five times gravity acceleration, the maximum stress was still below the allowable stress. The heat analysis results indicate that the maximum temperature on the detector box was ~56°C, which is within the detector operation temperature limit. The neutronics analysis results indicate that the detectors can be operated during the whole deuterium-deuterium phase without detector replacement. The electronics group and instrumentation and control group have also made good progress.